Cognitive functions in combat posttraumatic stress disorder - Havelka Meštrović, Ana (Array, 2020)
Posttraumatic stress disorder (PTSD) is associated with changes in cognitive functions. The aim of the study was to investigate differences in cognitive abilities between PTSD patients and healthy controls. As PTSD is often accompanied by comorbidity, the PTSD patients with comorbid diagnoses were also included in our study. The study participants included 254 Croatian combat veterans (60 PTSD and 194 PTSD plus comorbidity) and control group of 125 healthy Croatian military and civilian pilots. The diagnosis of PTSD was made by clinical scale for PTSD assessment (CAPS), while cognitive abilities were measured by Wechsler intelligence scale (WAIS-III-R) and Rey test (ROCFT). The study results have confirmed that there is a significant difference in cognitive functions between the PTSD patients and healthy controls regarding age and education. The PTSD patients (PTSD only and PTSD with comorbidity) have shown lower general intellectual abilities, reduced capacity of working, numerical and visual memory, and decreased executive functions when compared to healthy controls. These results are an additional contribution to a better understanding and determination of changes in cognitive functions that occur in combat PTSD as a result of traumatic stress.